Conservation and Use of Latin American Maize Diversity: Pillar of Nutrition Security and Cultural Heritage of Humanity - Guzzon, Filippo; Arandia Rios, Luis Walquer; Caviedes Cepeda, Galo Mario; Céspedes Polo, Marcia; Chávez Cabrera, Alexander; Muriel Figueroa, Jesús; Medina Hoyos, Alicia Elizabeth; Jara Calvo, Teófilo Wladimir; Molnar, Terence L.; Narro León, Luis Alberto; Narro León, Teodoro Patricio; Mejía Kerguelén, Sergio Luis; et al. (MDPI, 2022)
Latin America is the center of domestication and diversity of maize, the second most cultivated crop worldwide. In this region, maize landraces are fundamental for food security, livelihoods, and culture. Nevertheless, genetic erosion (i.e., the loss of genetic diversity and variation in a crop) threatens the continued cultivation and in situ conservation of landrace diversity that is crucial to climate change adaptation and diverse uses of maize. We provide an overview of maize diversity in Latin America before discussing factors associated with persistence of large in situ maize diversity, causes for maize landrace abandonment by farmers, and strategies to enhance the cultivation of landraces. Among other factors, maize diversity is linked with: (1) small-holder farming, (2) the production of traditional food products, (3) traditional cropping systems, (4) cultivation in marginal areas, and (5) retention of control over the production system by the farmers. On the other hand, genetic erosion is associated with substitution of landraces with hybrid varieties or cash crops, and partial (off-farm labor) or complete migration to urban areas. Continued cultivation, and therefore on-farm conservation of genetic diversity held in maize landraces, can be encouraged by creating or strengthening market opportunities that make the cultivation of landraces and open pollinated varieties (OPVs) more profitable for farmers, supporting breeding programs that prioritize improvement of landraces and their special traits, and increasing the access to quality germplasm of landraces and landrace-derived OPVs.